2008
DOI: 10.1111/j.1528-1167.2008.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of epilepsy and pharmacoresistant epilepsy in adults: A population‐based study in a Western European country

Abstract: SUMMARYPurpose: To determine the prevalence of epilepsy in a defined adult population and identify the frequency and principal features of pharmacoresistant epilepsy. Methods: From a population over 15 years of age residing in a medium-sized French city, all patients with epilepsy on June 30, 1995 were identified from multiple sources. Pharmacoresistance was defined as failure to control epilepsy by at least two firstline antiepileptic drugs, with a seizure frequency of at least one per month for 18 months. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
210
7
22

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(258 citation statements)
references
References 35 publications
19
210
7
22
Order By: Relevance
“…The prevalence of active epilepsy (patients with at least one seizure in the past 5 years), is 0.4–1.0% worldwide 1. In a study of one city in France, Picot et al 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of active epilepsy (patients with at least one seizure in the past 5 years), is 0.4–1.0% worldwide 1. In a study of one city in France, Picot et al 1.…”
mentioning
confidence: 99%
“…In a study of one city in France, Picot et al 1. found that 37.5% of patients with active epilepsy had suffered at least one generalized tonic–clonic seizure (GTCS).…”
mentioning
confidence: 99%
“…D'une part, leur effet prolongé ne permet pas de limiter leur action à la durée d'une crise, de sorte que la prise d'antiépileptiques affecte le fonctionnement normal du cerveau entre les ictus, donnant lieu à des effets secondaires indésirables (vertiges, somnolence, troubles de la vision). D'autre part, ces médicaments ont une action limitée face à la diversité des types cliniques d'épi-lepsie, dont on considère classiquement qu'au moins 20 à 30 % sont -ou deviennent -réfractaires au traitement (on parle d'épilepsie pharmaco-résistante) [41]. La neurochirurgie résective constitue actuellement la principale option alternative pour les patients pharmaco-résistants.…”
Section: Approches Optogénétiques Dans Le Traitement De L'épilepsieunclassified
“…Of the remaining percentage, approximately 30 % will be assigned to a more specific category within 2 years [8]. Approximately 20 to 30 % of patients with epilepsy have refractory epilepsy (i.e., seizures that persist, despite accurate diagnosis and carefully monitored treatment with antiepileptic drugs) [9]. Knowledge of the pathophysiology of childhood epilepsy has considerably increased with improvement of both neuroimaging and genetic techniques.…”
Section: Introductionmentioning
confidence: 99%